2020
DOI: 10.3390/plants9020187
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Analysis of the Essential Oil from Siparuna echinata (Kunth) A. DC. (Siparunaceae) of Ecuador and Isolation of the Rare Terpenoid Sipaucin A

Abstract: The phytochemical research on the species Siparuna echinata, collected in the Province of Loja (Ecuador), led to the isolation of a rare sesquiterpenoid, called Sipaucin A. The structure was confirmed by nuclear magnetic resonance (NMR) and mass spectrometry (MS). Furthermore, the essential oil of the fruits was obtained by hydrodistillation and analyzed by gas chromatography, coupled to mass spectrometry (GC-MS) and flame ionization detector (GC-FID). Twenty-seven compounds were identified in a polydimethylsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…Among the natural products the authors are interested in, we can cite essential oils (EOs) [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. According to the European Pharmacopeia, an EO is an “odorous product, usually of complex composition, obtained from a botanically defined plant raw material by steam distillation, dry distillation, or a suitable mechanical process without heating.…”
Section: Introductionmentioning
confidence: 99%
“…Among the natural products the authors are interested in, we can cite essential oils (EOs) [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. According to the European Pharmacopeia, an EO is an “odorous product, usually of complex composition, obtained from a botanically defined plant raw material by steam distillation, dry distillation, or a suitable mechanical process without heating.…”
Section: Introductionmentioning
confidence: 99%
“…We also observe that the nutrient content of the soil and the plant, as well as the chemical composition of the essential oil, are strongly influenced by the sampling location. Other studies found α-pinene (24.3%), β-pinene (21.7%) and myrcene (11.3%) in Siparuna echinate (Khunt) as major compounds [ 7 ], following these patterns, germacrene D (23.2% and α-pinene (7.0) were found to be major compounds in S. macrotepala [ 32 ]. A study of S. schimpffii Diels, which is used as an analgesic by the Shuar people of the Ecuadorian Amazon, specifically in the province of Morona Santiago, representative components were: germacrene D (35.34%), bicyclogermacrene (8.73%), γ-muurulene (7.04%), germacrene B (6.36%) and trans-cadina-1 (2), 4-diene (5.16%), which was similar with the chemical composition from our study, with the exception of germacrene D [ 33 ].…”
Section: Discussionmentioning
confidence: 89%
“…In this context, several studies shown that the Siparunaceae family has great economic, medicinal and phytochemical importance [ 6 , 7 ]. The fruits and leaves of certain species are used as traditional medicines of South and Central America to treat fever, cough, gastrointestinal diseases and rheumatism, and also this species is used as timber [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among natural products, a special interest exists in essential oils (EOs) [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ], whose main property is their aroma. In fact, they are defined in the European Pharmacopoeia as “odorous products, usually of complex composition, obtained from a botanically defined plant raw material by steam distillation, dry distillation, or a suitable mechanical process without heating.…”
Section: Introductionmentioning
confidence: 99%